Nasolacrimal duct obstruction with obstructive nasal deformity; is synchronous nasal surgery necessary? - Toplu, Yuksel; Bayındır, Tuba; Balbaba, Mehmet; Kalcioglu, M.tayyar; Sapmaz, Emrah; Karatas, Erkan (My University, 2021)
The aim of this study was to evaluate the necessity of the simultaneous additional nasal surgery to increase success rate of the endoscopic dacryocystorhinostomy operation, in the patients with nasolacrimal duct obstruction and obstructive nasal deformity. One hundred and thirty patients with nasolacrimal duct obstruction and obstructive nasal deformity (59 were female and 71 male, age ranged between 31 and 82 years, mean=60.3 years) were included in this study. Patients with nasolacrimal duct obstruction were divided into two main groups (group A and B) and six subgroups (A1, A2, A3 and B1, B2, B3) according to the presence of obstructive nasal deformity and applied operation techniques. The success and complications rates of this groups were evaluated. The success rates of endoscopic dacryocystorhinostomy in the additional nasal surgery performed group (Group A) were not statistically significant higher than the group without additional nasal surgery (Group B). Complications rate of group A (26.08%) were statistically significant higher than group B (9.8%). In patients with complications, the average success rate of endoscopic dacryocystorhinostomy surgery (70.8%) was statistically significant lower than in patients with no complications (88.6%), respectively. Additional nasal surgery has no statistically significant effect on the success of the endoscopic dacryocystorhinostomy surgery. Developing complications was statistically affect the success rate of endoscopic dacryocystorhinostomy surgery. Due to these reasons, contrary to the general idea, we believe that, to increase the success rate of the endoscopic dacryocystorhinostomy surgery, additional nasal surgery is unnecessary in patients with nasolacrimal duct obstruction and obstructive nasal deformity.
Keywords: Tıbbi Araştırmalar Deneysel; Kulak; Burun; Boğaz; Cerrahi